2011
DOI: 10.1002/dvdy.22575
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of neuron-specific gene family member 1 in brain and germ cells: Implications for the regulation of germ-line development by brain

Abstract: Vesicular acidification at early endosomes dissociates endocytosed receptor-ligand complexes. The ligands, receptors, or both are then directed to late endosomes for degradation or recycled back to the plasma membrane. Of neuron-specific gene (NSG) family members, early endosomal protein neuron-specific gene family member 1 (NSG1) is the most important in receptor recycling. In this study, we characterized chicken NSG1 (cNSG1). We found several functional sites related to endocytotic machinery in cNSG1 that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
3
10
0
Order By: Relevance
“…Induced alteration (overexpression or knockdown) of several genes causing DNA damage were reported to cause spontaneous mutations on the HPRT locus also due to unbalance of dNTP pool. 3,8,10,65 At the same time, the expression levels of apoptosis genes were increased, indicating that the knockdown of chicken cyclin F like gene causes germ cells impairment and results in apoptosis in correlation with our in vitro findings. 77 In this study, the cyclin F like knockdown PGCs resulted in spontaneous mutations, including frequent deletions and transitions on the chicken HPRT locus also, and had a low proportion of S-phase cells, suggesting that aberrant DNA damage lead to a failure of DNA replication during the cell cycle.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Induced alteration (overexpression or knockdown) of several genes causing DNA damage were reported to cause spontaneous mutations on the HPRT locus also due to unbalance of dNTP pool. 3,8,10,65 At the same time, the expression levels of apoptosis genes were increased, indicating that the knockdown of chicken cyclin F like gene causes germ cells impairment and results in apoptosis in correlation with our in vitro findings. 77 In this study, the cyclin F like knockdown PGCs resulted in spontaneous mutations, including frequent deletions and transitions on the chicken HPRT locus also, and had a low proportion of S-phase cells, suggesting that aberrant DNA damage lead to a failure of DNA replication during the cell cycle.…”
Section: Discussionsupporting
confidence: 87%
“…NANOG and POUV are pluripotency-as well as germ cell-marker genes, and strongly detectable in the chicken intrauterine embryos and in the PGCs until at least E7.5-8.0, a time in which the PGCs differentiate into oogonia in female but not in male. 55,65 The chicken cyclin F like knockdown PGCs robustly underwent apoptotic cell death due to increased DNA damage in the cells as evidenced by the increased level of γ-H2A.X signal and apoptosis-related genes. 55,64 The pre-meiotic marker STRA8 is expressed in the chicken PGCs from E6.5, and upregulated female-specifically from E12.5.…”
Section: Discussionmentioning
confidence: 99%
“…We newly detected the expression of a Na + /K + -transporting ATPase (Atp1a1, Atp1b1) in the OE; this ATPase modulates membrane potential [ 154 ]. We also detected Nsg1 in the OE; this molecule is involved in regulating receptor recycling [ 155 ]. The expression of both genes is important for olfactory signaling, as the adjustment of ion homeostasis is the basis for the depolarization of neurons and the recycling of receptors.…”
Section: Non-gpcr Membrane Proteinsmentioning
confidence: 99%
“…Nsg1 or neuron-specific gene family member 1 is a type of protein preferentially located in the brain, neuroendocrine glands, and spinal cord. The role of this gene was not clearly defined, but studies have shown that Nsg1 protein function in neurons and germ cell chemotaxis and endocytotic machinery (Rengaraj et al 2011). Moreover, a recent study has reported that Nsg1 protein was involved in trafficking of neuron-glia cell adhesion molecule (NgCAM).…”
Section: Discussionmentioning
confidence: 98%